Telmisartan prevents development of obesity and normalizes hypothalamic lipid droplets. Issue 1 (January 2020) - Rawish, Elias; Nickel, Laura; Schuster, Franziska; Stölting, Ines; Frydrychowicz, Alex; Saar, Kathrin; Hübner, Norbert; Othman, Alaa; Kuerschner, Lars; Raasch, Walter
Abstract : The AT1 receptor blocker telmisartan (TEL) prevents diet-induced obesity. Hypothalamic lipid metabolism is functionally important for energy homeostasis, as a surplus of lipids induces an inflammatory response in the hypothalamus, thus promoting the development of central leptin resistance. However, it is unclear as to whether TEL treatment affects the lipid status in the hypothalamus. C57BL/6N mice were fed with chow (CONchow ) or high-fat diet (CONHFD ). HFD-fed mice were gavaged with TEL (8 mg/kg/day, 12 weeks, TELHFD ). Mice were phenotyped regarding weight gain, energy homeostasis, and glucose control. Hypothalamic lipid droplets were analyzed by fluorescence microscopy. Lipidomics were assessed by performing liquid chromatography-mass spectrometry in plasma and hypothalami. Adipokines were investigated using immunosorbent assays. Glial fibrillary acidic protein (GFAP) was determined by Western blotting and immunohistochemical imaging. We found that body weight, energy homeostasis, and glucose control of TEL-treated mice remained normal while CONHFD became obese. Hypothalamic ceramide and triglyceride levels as well as alkyne oleate distribution were normalized in TELHFD . The lipid droplet signal in the tanycyte layer was higher in CONHFD than in CONchow and returned to normal under TELHFD conditions. High hypothalamic levels of GFAP protein indicate astrogliosis of CONHFD mice while normalized GFAP, TNFα, and IL1α levels of TELHFD mice suggest that TEL prevents hypothalamic inflammation. In conclusion, TEL has anti-obese efficacy and prevented lipid accumulation and lipotoxicity, which is accompanied by an anti-inflammatory effect in the murine hypothalamus. Our findings support the notion that a brain-related mechanism is involved in TEL-induced weight loss.